The sinner. Season three [videorecording (DVD)]. - Pullman, Bill; Bomer, Matthew, 1977-; Messina, Chris; Hecht, Jessica, 1965- (Universal Studios, 2020)
The third installment follows Detective Harry Ambrose as he begins a routine investigation of a tragic car accident on the outskirts of Dorchester, in upstate New York. Ambrose uncovers a hidden crime that pulls him into the most dangerous and disturbing case of his career.